IFRS CONVERGENCE AND EARNINGS MANAGEMENT - Trisninik Ratih Wulandari, Juliati, Arum Kusumaningdyah Adiati (ITB AAS INDONESIA, 2017)
This study aims at providing empirical evidence about the impacts of IFRS convergence on earnings management and examining the differences of the level of earnings management between before and after full IFRS convergence.The research objects were manufacturing companies registered on the Indonesia Stock Exchange (BEI) for 4 years (2010-2013). The sampling technique used was purposive sampling. The number of samples taken from the purposive sampling for each year was 85 companies. The main variables used in this study were IFRS and earnings management. The hypothesis analysis used multiple regression analysis of data by using discretionary accruals developed by Jones (1991) and the analysis of t-test difference test.The results show no difference between the earnings in the period of before and after convergence. The results of the difference test analysis also reveal that there is no difference in the level of earnings management between the period of before and after convergence. Based on this study it can be concluded that the IFRS convergence does not guarantee a decrease in earnings management of manufacturing companies listed on BEI.Keywords: earnings management, IFRS convergence, discretionary accrual